PENGEMBANGAN VIDEO SEJARAH PERKEMBANGAN ISLAM DI KOTA JAMBI BERBASIS YOUTUBE SEBAGAI MEDIA PEMBELAJARAN SEJARAH KELAS XI DI SMA ADHYAKSA 1 KOTA JAMBI - Radmansyah, Rezi; Rahim, Arif (Universitas Batanghari Jambi, 2022)
The purpose of this development research is to find out the development of Youtube-Based Learning Media in learning history material at Adhyaksa 1 Jambi High School. To see student responses when learning to use YouTube media. The development model used is ADDIE which consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The subjects of this study were students of SMA Adhyaksa 1 Jambi class XI. The feasibility of learning media refers to the results of the media assessment by experts on the developed learning media. The YouTube-based history learning media on the History of Islamic Development in Jambi City which was developed has met the criteria for valid/valid use for class XI high school students. The results of the media assessment by validator I obtained a value of 90.3 with the eligibility criteria of Very Valid. The results of the assessment of the validator II material obtained a value of 87.5 with the eligibility criteria of Very Valid. The results of the history teacher's assessment on the media aspect obtained a value of 100 with very good criteria and the material aspect obtained a value of 97.5 with very good criteria. The results of the assessment of student responses in the first trial obtained a percentage of 81% with the eligibility criteria Very Good, the second trial 90% with the eligibility criteria Very Good, and the third trial obtained a percentage of 90.6% with the eligibility criteria Very Good.